Association of BCC Module Roll-Out in SHG meetings with changes in complementary feeding and dietary diversity among children (6–23 months)? Evidence from JEEViKA in Rural Bihar, India - Sudipta Mondal; William Joe; Santosh Akhauri; Putul Thakur; Abhishek Kumar; Narottam Pradhan; Prasann Thatte; Rakesh Kumar Jha; Apolenarius Purty; Indrajit Chaudhuri (PLoS ONE, 2023)
Objectives Child dietary diversity is very low across rural communities in Bihar. Based on the experience of behavior change communication (BCC) module roll out in self-help group (SHG) sessions in rural Bihar, this study aims to assess the impact of the intervention on child dietary diversity levels in the beneficiary groups. Methods The study is based on a pre-post study design whereby child dietary diversity is examined for a sample of 300 children (6–23 months old from 60 village organizations) during both pre-intervention as well as post-intervention phase. The latter consists of two types of group viz. a) children whose mothers were directly exposed to BCC module in SHGs sessions and b) those who were non-participants but may have indirect exposure through spillovers of BCC activities. Econometric analysis including logistic regression as well as propensity score matching techniques are applied for estimating the changes in dietary diversity in the post-intervention phase. Results During the pre-intervention phase, 19% of the children (6–23 months) had adequate dietary diversity (eating from at least 4 out of 7 different food groups) and this increased to 49% among the exposed group and to 28% among the non-exposed group in the post-intervention phase. The exposed group have an odds ratio of 3.81 (95% CI: 2.03, 7.15) for consuming diverse diet when compared to the pre-intervention group. The propensity score matching analysis finds a 33% average treatment effect on the treated (ATT) for the group participating in BCC sessions at SHG events. Conclusion BCC roll out among SHG members is an effective mode to increase dietary diversity among infants and young children. The impact on child dietary diversity was significantly higher among mothers directly exposed to BCC modules. The BCC module also improved knowledge and awareness levels on complementary feeding and child dietary diversity.